2013
DOI: 10.1007/s00726-013-1496-y
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms and Maillard reaction products: a review of the literature and recent findings

Abstract: Research on the impact of Maillard reaction products (MRPs) on microorganisms has been reported in the literature for the last 60 years. In the current study, the impact of an MRP-rich medium on the growth of three strains of Escherichia coli was measured by comparing two classic methods for studying the growth of bacteria (plate counting and optical density at 600 nm) and by tracing MRP utilisation. Early stage and advanced MRPs in the culture media were assessed by quantifying furosine and N (ε) -carboxymeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…The decreases of enterobacteria observed among humans after BD consumption were correlated with increased intakes of HMF and CML, whereas Escherichia / Shigella growth was negatively correlated only with HMF intake, without correlation with CML (Table ). Helou et al observed that CML has no effect on E. coli growth, thereby concluding that these MRP are not consumed by these bacteria, which is in line with the absence of correlation found in the present experiments. Other authors have found that melanoidins of food‐origin have an antimicrobial activity against E. coli , by causing irreversible damages to its inner and outer membranes.…”
Section: Resultssupporting
confidence: 92%
“…The decreases of enterobacteria observed among humans after BD consumption were correlated with increased intakes of HMF and CML, whereas Escherichia / Shigella growth was negatively correlated only with HMF intake, without correlation with CML (Table ). Helou et al observed that CML has no effect on E. coli growth, thereby concluding that these MRP are not consumed by these bacteria, which is in line with the absence of correlation found in the present experiments. Other authors have found that melanoidins of food‐origin have an antimicrobial activity against E. coli , by causing irreversible damages to its inner and outer membranes.…”
Section: Resultssupporting
confidence: 92%
“…For example, polyphenol-rich beverages when con- sumed at meal times can affect starch digestion by inhibiting starch-degrading enzymes in the upper gut and thus blunting postprandial glucose peaks. Similarly, the Maillard reaction in cooked foods can increase the recalcitrance of food macromolecules to digestion, leading to increased survival of both carbohydrates and proteins until they reach the colon (48). However, once these food compounds reach the colon, they become available to the fermentative activities of the human colonic microbiota.…”
Section: Weissella Leuconostoc Staphylococcus Streptococcus Andmentioning
confidence: 98%
“…However, once these food compounds reach the colon, they become available to the fermentative activities of the human colonic microbiota. Recent metagenomic studies have highlighted that the gut microbiota is specifically evolved for the digestion of complex plant polysaccharides, possessing a range of polysaccharide-and glycan-degrading enzymes not present in the human genome (48). In this way, the human gut microbiota can be viewed as a closely coevolved microbial partner to the human genome, extending host-encoded functions and allowing the host to derive energy and other biologically active compounds from food components that would otherwise remain inaccessible and be excreted as waste.…”
Section: Weissella Leuconostoc Staphylococcus Streptococcus Andmentioning
confidence: 99%
“…In the diabetic heart, glucose forms covalent adducts with the plasma proteins through a non-enzymatic reaction between the free amino groups of proteins and carbonyl groups of reducing sugars, resulting in the formation of stable glycosylation products by Amadori rearrangement, which is called glycation (9194). Glycated proteins undergo a series of oxidation, dehydration, and cyclization reactions to form long-lived AGEs (95, 96).…”
Section: Increased Formation Of Advanced Glycation End Products (Ages)mentioning
confidence: 99%